A method for personalizing the training regimen for elite female athletes in modern pentathlon over an annual training cycle - Sevdalev S.V.; Borovaya V.A.; Vrublevskiy E.P. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to create and support a method for personalizing the year-long training of elite athletes in modern pentathlon. Methods and structure of the study. The research was conducted at the Gomel Olympic Reserve Center for Applied Sports and the Scientific Research Laboratory of the Gomel State University named after F. Skorina. The study aimed to establish a systematic approach to personalizing the training of female athletes in modern pentathlon. The developed algorithm was implemented in the training of six elite athletes. Results and conclusions. A series of steps has been devised to tailor the training of athletes in the sport of modern pentathlon, which encompasses a range of activities. These include: a) Identifying the collective and personal characteristics of the athletes’ competitive performance and readiness, which serves as the foundation for creating personalized training plans. b) Establishing the individualized approach to training, selecting the appropriate tools, and determining their distribution within the annual training cycle. c) Considering the interplay between training load, physical attributes, psychological factors, and biorhythms, we design a personalized training program for the athlete, spanning an entire annual cycle. The final phase of this process involves monitoring the planned and actual performance indicators, making adjustments to the training regimen, and evaluating the athlete’s performance in both training and competition. The efficacy of the algorithm we developed is evident from the substantial enhancement in the physical and athletic performance of the athletes who participated in the study, as well as the improvement in their results in the events of modern pentathlon.